Linked out? A field experiment on discrimination in job network formation - Yulia Evsyukova; Felix Rusche; Wladislaw Mill (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
We assess the impact of discrimination on Black individuals' job networks across the U.S. using a two-stage field experiment with 400+ fictitious LinkedIn profiles. In the first stage, we vary race via AI-generated images only and find that Black profiles' connection requests are 13 percent less likely to be accepted. Based on users' CVs, we find widespread discrimination across social groups. In the second stage, we exogenously endow Black and White profiles with the same networks and ask connected users for career advice. We find no evidence of direct discrimination in information provision. However, when taking into account differences in the composition and size of networks, Black profiles receive substantially fewer replies. Our findings suggest that gatekeeping is a key driver of Black-White disparities.
Keywords: J71; J15; C93; J46; D85; 330; Discrimination; Job Networks; Labor Markets; Field Experiment